2018
DOI: 10.6036/8495
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fibers Addittion on the Properties of Hydraulic Lime Based Mortars

Abstract: The influence of carbon and basalt fibres addition on hydraulic lime mortars mechanical properties and durability has been studied. The objective is to evaluate the possible use in restoration of architectural heritage, as an alternative to Portland cement because of the pathological processes that the latter causes. To assess the effect, the obtained results have been compared with two reference mortars: hydraulic lime with no additions and basalt fibres. The amount of fibres to be incorporated is questioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been shown that the addition of synthetic fibers in the mold matrix makes it possible to stop cracking in the face of bending forces and improves the internal cohesion of the conglomerate material [62]. In addition, the compression resistances obtained are indicative of the quality of mortars made from recycled aggregate and reinforced with fibers, since they provide information on the capacity of the materials tested when it comes to bearing loads without breaking up [63]. In this way, it has been possible to observe how the addition of synthetic fibers in the percentages indicated in the research improves the mechanical strength of the mortars; similar results have also been obtained by other researchers who used natural fibers during the mixing process to improve the mechanical properties in this type of material [64].…”
Section: Mechanical Resistance To Flexural and Compressionmentioning
confidence: 99%
“…It has been shown that the addition of synthetic fibers in the mold matrix makes it possible to stop cracking in the face of bending forces and improves the internal cohesion of the conglomerate material [62]. In addition, the compression resistances obtained are indicative of the quality of mortars made from recycled aggregate and reinforced with fibers, since they provide information on the capacity of the materials tested when it comes to bearing loads without breaking up [63]. In this way, it has been possible to observe how the addition of synthetic fibers in the percentages indicated in the research improves the mechanical strength of the mortars; similar results have also been obtained by other researchers who used natural fibers during the mixing process to improve the mechanical properties in this type of material [64].…”
Section: Mechanical Resistance To Flexural and Compressionmentioning
confidence: 99%
“…It should be noted that there are studies that try to combine different types of reinforcing fibers to check whether they act in a synergistic mutually beneficial manner [29]. This is the case of recent investigations with additions of polypropylene fiber and isostatic graphite filler (IGF) at 0.6% by volume and 25% by weight, respectively, which have shown better mechanical and thermal results and a greater decrease in porosity when acting together [30].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain, almost 2% of buildings are in a dilapidated condition and 7.6% are in poor condition. That means that there are more than 963,300 buildings that should undertake works of integral restoration [1,2].…”
Section: Introductionmentioning
confidence: 99%